PROSES PENDANGKALAN DI PANTAI DAN LEPAS PANTAI CIREBON AKIBAT LAJU SEDIMENTASI ASAL DARATAN YANG TINGGI - Setyadi, D.; C.D Aryanto, Noor (Jurnal Geologi dan Sumberdaya Mineral, 2008)
The litology of Cirebon coastal area is alluvium from the Quarternary sediment. The emerged land in Cirebon coastal area is very wide due to a very flat coastal morphology and very high sedimentary in flux, especially in the river mouth area. The bat imetric map at Cirebon waters shows that the shallow water is in Kalijaga river mouth. Sediments are thicker towards Kalijaga and Sukalila river mouths. Further more, the sediment was deposited offshore and to the planning harboursites. Ingeneral, fluvial current is more dominant than longshore and marine currents and it is responsible for sedimentation along the coastalline and the river mouth. Keywords: emergedland, sedimentary influx, Cirebon waters